A Study on Zepto’s Deceptive Promotional and Pricing Strategies in Mumbai’s Quick-Commerce Sector. - Sanchita Datta, Renu Khandelwal, Iqra Khatri, (European Economic Letters (EEL), 2026)
This study examines deceptive promotional and pricing strategies used by Zepto within India's quick‑commerce industry. Using a structured survey of 71 respondents and secondary literature sources, the research evaluates practices such as hidden charges, misleading cashback promotions, urgency‑driven marketing tactics, and device‑based price discrimination. The findings indicate that a majority of respondents perceive Zepto’s promotional strategies as misleading, particularly due to hidden fees and exaggerated discount claims. Although consumers recognize these practices, many continue to use the platform due to the convenience of rapid delivery. The study concludes that stronger regulatory oversight, improved transparency, and ethical marketing standards are necessary to sustain consumer trust in digital marketplaces.